Latossolos com horizonte subsuperficial escurecido, na região de Viçosa - Ribeiro , Antônio Carlos; Resende , Mauro; Fernandes , Bairon (Revista Ceres, 2025)
This work caracterizes the soils developed on the coluvial landscape in the Viçosa area, Minas Gerais, Brazil. The soil landscape was sampled on a grid of approximately 20 by 20 meters using a soil auger. These soils occupy small but well distributed areas throughout the region.